The Princeton Companion to Applied Mathematics, Edited by Nicholas J. Higham, Associate Editors: Mark R. Dennis, Paul Glendinning, Paul A. Martin, Fadil Santosa and Jared Tanner, Princeton University Press, Princeton, NJ, 2015, xvii + 994 pp, ISBN: 978-3-11-033117-2/pbk; 978-3-11-033118-9/ebook. - COBZAȘ, S. (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
As the editor writes in the Preface \The Princeton Companion to Applied Mathematics describes what applied mathematics is about, why it is important, its connections with other disciplines, and some of the main areas of current research." We also reproduce here the nice words of Paul Halmos quoted in Editor's (NJH) article What is applied mathematics?